Minimal guidewire length for central venous catheterization of the right subclavian vein: A CT-based consecutive case series. Issue 3 (May 2022) - Adrian, Maria; Bengtsson, Pär; Borgquist, Ola; Bozovic, Gracijela; Kander, Thomas
Background: Central venous catheter (CVC) misplacement occurs frequently after right subclavian vein catheterization. It can be avoided by using ultrasound to confirm correct guidewire tip position in the lower superior vena cava prior to CVC insertion. However, retraction of the guidewire during the CVC insertion may dislocate the guidewire tip from its desired and confirmed position, thereby resulting in CVC misplacement. The aim of this study was to determine the minimal guidewire length required to maintain correct guidewire tip position in the lower superior vena cava throughout an ultrasound-guided CVC placement in the right subclavian vein. Methods: One hundred adult patients with a computed tomography scan of the chest were included. By using multiplanar reconstructions from thin-sliced images, the distance from the most plausible distal puncture site of the right subclavian vein to the optimal guidewire tip position in the lower superior vena cava was measured (vessel length). In addition, measurements of equipment in common commercial over-the-wire percutaneous 15–16 cm CVC kits were performed. The 95th percentile of the vessel length was used to calculate the required minimal guidewire length for each CVC kit. Results: The 95th percentile of the vessel length was 153 mm. When compared to the calculated minimal guidewire length, the guidewires were up to 108 mm too short in eight of eleven CVC kits. Conclusion: After confirmation of a correct guidewire position, retraction of the guidewire tip above the junction of the brachiocephalic veins should be avoided prior to CVC insertion in order to preclude dislocation of the catheter tip towards the right internal jugular vein or the left subclavian vein. This study shows that many commercial over-the-wire percutaneous 15–16 cm CVC kits contain guidewires that are too short for right subclavian vein catheterization, i.e., guidewire retraction is needed prior to CVC insertion.